Rheological, mineralogical and strength variability of concrete due to construction water impurities - Awoyera, Paul O. (2020)
Various national and international standards recommend potable water for mixing concrete; however, the availability of potable water is virtually a daunting task in some developing communities. Concrete workers in such environments tend to utilize any available water for mixing concrete, and this may be detrimental to the quality of the concrete being produced. This study investigates the rheological, mineralogical and strength variability of concrete due to construction water impurities. Water samples were collected from four different construction sites within Southwestern region of Nigeria for production of concrete. The physical and chemical properties of the waters were determined so as to measure their rate of contamination, prior to their use for mixing concrete. The rheological properties of the fresh concrete, compressive strength, split tensile strength, and microscale features of hardened concrete, that were produced with each water sample were determined. From the results, the rheological features of concrete were found not to be affected by water impurities, however, the mechanical test results revealed about 10% reduction in strength between concrete made with water having least and higher concentration of impurities. Also, it was evident from the microscale tests that the water impurities do alter the hydration rate of concrete, which results in strength reduction. The study suggests pretreatment of concrete mixing water before use in order to avoid its damaging effect on concrete life.